Deep-water species assemblages on the trawlable bottoms of the Central Mediterranean: Changes or not over time? - Maiorano, Porzia; Ricci, Pasquale; Chimienti, Giovanni; Calculli, Crescenza; Mastrototaro, Francesco; D’Onghia, Gianfranco (Frontiers in Marine Science, 2022)
Deep-sea communities are impacted by several anthropogenic activities, such as fisheries, which still remain one of the most damaging on the marine environments in terms of biodiversity loss and habitat degradation. The north-western Ionian Sea (Central Mediterranean) experienced long-standing trawl fishing activity with the exploitation of deep-sea demersal resources. The integrate analysis with data of both benthic, demersal and benthopelagic species collected during a time series of experimental trawl survey, yearly carried out in the Ionian basin down to 800 m in depth, allowed to asses the current status of the Ionian deep-sea faunal assemblages and their potential changes overtime. Multivariate analysis and univariate indices, modelled using Generalized Additive Model (GAM) framework, confirm a depth zonation pattern of deep-sea faunal assemblages in the study area, with the presence of two distinct epibathyal and mesobathyal groups. GAM also highlighted a temporal effect on the biodiversity indices, with significant negative trends of diversity and evenness indices as well as a significant increasing of dominance one, over the study period 2012-2020. The benthic community is characterised by more generalist species and a simplified structure, with a severe depletion in habitat-former taxa whereas the demersal and benthopelagic fauna of the Ionian Sea show a general stability in the overall structure if compared with previous studies lasting over two decades. The presence of complex and heterogenous habitats unsuitable for trawl, like cold-water coral communities and canyon systems, provide Essential Fish Habitats (EFHs) for commercial species, acting as potential renewal areas for exploited resources in the neighbouring fishing grounds. These findings encourage an ecosystem-based management including spatial considerations for the objectives of biodiversity conservation combined with those of management of fishery resources.